Pengembangan Aplikasi Berbasis Multimedia pada Pembelajaran Tematik Kelas III Sekolah Dasar - Bakhtiar, Faisal Azmi (Mimbar Sekolah Dasar, 2018)
The purpose of this study is to analyze the feasibility and practicality of multimedia-based products on thematic learning of earth change subtheme. This research was conducted on the third-grade students of Elementary School with a total number of 156 students as the respondents. This research used research development (R D) design of Dick, Carey and Carey model. To see the effectiveness of the product developed by the group field test with 150 students. Result of t-test analysis showed tvalue = -8.97 ttable = - 1.962 at significance level Î± = 0,05. There was a significant difference between the pre-test 53.56 post-test 67.71 and the difference of 15.15. These results showed that multimedia developed effectively used in thematic learning. The results of student responses showed an average score of 79.75%. Response analysis results can be interpreted that multimedia-based applications are worth it to apply.